Colorimetric assaying of exosomal metabolic biomarkers - Yan, Evelias (2023)
Exosomes released into the extracellular matrix have been reported to contain metabolic biomarkers of various diseases. These intraluminal vesicles are typically found in blood, urine, saliva, breast milk, cerebrospinal fluid, semen, amniotic fluid, and ascites. Analysis of exosomal content with specific profiles of DNA, microRNA, proteins, and lipids can mirror their cellular origin and physiological state. Therefore, exosomal cargos may reflect the physiological processes at cellular level and can potentially be used as biomarkers. Herein, we report an optical detection method for assaying exosomal biomarkers that supersedes the state-of-the-art time consuming and laborious assays such as ELISA and NTA. The proposed assay monitors the changes in optical properties of poly(3-(4-methyl-3'-thienyloxy) propyltriethylammonium bromide) upon interacting with aptamers/peptide nucleic acids in the presence or absence of target biomarkers. As a proof of concept, this study demonstrates facile assaying of microRNA, DNA, and advanced glycation end products in exosomes isolated from human plasma with detection levels of ~1.2, 0.04, and 0.35 fM/exosome, respectively. Thus, the obtained results illustrate that the proposed methodology is applicable for rapid and facile detection of generic exosomal biomarkers for facilitating diseases diagnosis.